Head Bath: As a Specific Trigger For Migraine and Tension-Type Headaches - Gonen, Murat; Aytac, Emrah; Mungen, Bulent (Journal Neurological Sciences, 2017)
Aim: Head bath has recently been described as a trigger in migraine patients for migraine headaches. In this study we aimed to investigate the characteristic of headaches triggered by head bath in migraine patients. Material and methods: Patients with headaches developing after head bath were identified reviewing medical records of 990 migraine patients registered to our Headache Unit and characteristics of headache were comprehensively evaluated in these cases by inviting them to control visit. Results: It was found that head bath-triggered migraine headaches occurred in 36 of 990 (3.6 %) migraine patients with or without aura. In addition, in 14 (1.4 %) migraine patients, it was found that head bath-triggered non-migraine headaches with bilateral localization that are non-throbbing, less severe and shorter than migraine headaches and not accompanied by autonomic symptoms and that spontaneously resolve in most cases and can be prevented by hair drying. The non-migraine headaches developing in these cases met diagnostic criteria for episodic tension-type headaches. Conclusion: In patients with migraine, interictal sensitization present at interictal period (between migraine headaches) can predispose onset of migraine and tension-type headaches. In some cases, onset of migraine headaches on some occasions while tension-type headaches on other occasions by head bath suggests that similar mechanisms are involved in the triggering migraine and tension-type headaches.
Baş banyosu: Migren ve gerilim tipi baş ağrisinda özel bir tetikleyici özet
Keywords: Migraine; head bath; tension-type headache; trigger